The effect of training in Two methods to develop Distinctive Speed Power and some basic skills - Taher Mandeel, Ammar; Nafea Kamil, lhab; Mohamed Headan, Hussam; Saad Ahmed, Omar (International Journal of Psychosocial Rehabilitation, 2020)
The game of handball in the world has witnessed a remarkable development in recent years in the physical, skill and planning aspects, so modern play was characterized by speed, strength and elongation in accurate technical preparation, and most coaches did not follow the scientific foundations in developing the strength distinguished by speed by other scientific methods, including circular training and stations, and through the experience of the researcher Being a player and trainer for the former national team and a member of the Coaches Committee, he currently felt the use of these two methods to develop the distinctive force with speed and some basic handball skills, which is better in development. The objectives of the research are to identify the effect of the training curriculum in a circular training method on developing the force marked by speed and some basic handball skills. Knowing the effect of the training method in the stations method in developing the distinctive force with speed and some basic goals in handball. Knowing which methods (circular, stations) are better in developing the distinctive strength in speed and some basic skills in handball. Hypotheses of the research, and the presence of statistically significant significant differences using the method of circular training in the development of the Distinctive Speed Powerand some basic foals by hand. The presence of statistically significant differences using the stations method in developing the Distinctive Speed Power and some basic handball skills. The presence of statistically significant differences between the use of my technique (circular training and stations) in developing Distinctive Speed Power and some basic goals with handball. As for the third semester, the experimental method was used for its suitability to the nature of the research, and the sample included 24 players from the training center in Baquba who were divided into two homogeneous groups, one of which uses the method of circular training and the other of the station style, as well as the tools and the selection of appropriate tests for the strength distinguished by speed and basic handball skills, exploratory experiences, curriculum design, and statistical methods. Then the researcher prepared some conclusions and recommendations related to the research.